Association between Local Illumination and Visual Fatigue among the Research and Development Staffs of Industry. - A. R., Mashkoori; S., Asadi; A. R., Yari; Z., Allahdadi; Z., Gharlipour; A. R., Koohpaei (International Archives of Health Sciences)
Aims: Work proper lighting means a safe, healthy and comfort conditions for work under a lighting system that includes qualitative and quantitative features. This study aimed to evaluate the surface local lighting of works and eye fatigue among research and development staffs of an automotive industry. Instrument & Methods: In this descriptive study in Research and Development Department of an automotive industry in 2015, 126 official staffs were selected randomly. A demographic questionnaire and the Visual Fatigue Questionnaire (Persian Version) were used for data gathering. Hagner EC1 Luxmeter was used to measure the local lighting. Data were analyzed by SPSS 20 software, through descriptive statistics. Findings: The lighting in 382 stations (75.8%) was improper and less than standard. The minimum and maximum intensity of light was between 22.4lux in station 2 (inventory department) and 581lux in station 4 (systems and methods department). The overall intensity in more than 50% units, except the Systems and Methods Department, were less than the standard (300lux). 40.4% of the participants had severe eye fatigue, 28.6% had moderate visual fatigue, 28.6% had low visual fatigue and only 2.4% had no visual fatigue. The average of visual fatigue was 3.50±1.97. Conclusion: The workplace lighting and the eye fatigue of computer users in the Research and Development Department of the studied automotive industry are not in an acceptable condition.